Design, syntheses and applications of chiral transition metal complexes bearing phosphorus-containing ligands - Yang, Xiangyuan (2015)
A series of optically active tertiary phosphine compounds were prepared via catalytic asymmetric hydrophosphination of specially designed substrates. The C-stereogenic phosphines obtained were used in the formation of symmetrical PC(aryl)P, unsymmetrical PC(aryl)N and NC(sp3)X (X = O, S) transition metal pincer complexes, as well as novel copper(I) clusters. This work focuses on the syntheses, purification, characterization and application of the pincer complexes in asymmetric transformations such as hydrophosphination reactions. A regio-divergent hydrophosphination protocol involving a judicious choice of chiral phosphine−palladium(II) catalyst was successful in generating either the 1,4- or 1,6-adduct selectively from diunsaturated substrates. Subsequently, detailed investigations of the stereo-control imparted by the pincer architecture allowed the preparation of highly efficient catalysts which provided excellent regio- and stereo-selectivity in the asymmetric conjugate addition of phosphine nucleophiles to activated olefins.